Comparison of pattern of disease progression and prevalence of acquired T790M mutation in Malaysia patients with EGFR mutant lung adenocarcinoma upon failure of first-line afatinib, gefitinib and erlotinib - Chai, Chee Shee; Lin, O. Po; Liam, Chong Kin; Pang, Yong Kek; Ho, G. F.; Alip, A.; Wong, Chee Kuan; Poh, Mau Ern; Tan, Jiunn Liang (Oxford university press, 2019)
Abstract Background Patients receiving first-line afatinib, gefitinib or erlotinib for epidermal growth factor receptor (EGFR) mutant advanced non-small cell lung cancer develop progression of disease (PD) after an average of 9-13 months.